On the Edge Between Digital and Physical: Materials to Enhance Creativity in Children. An Application to Atypical Development - Ponticorvo, Michela; Sica, Luigia Simona; Rega, Angelo; Miglino, Orazio (Frontiers in Psychology, 2020)
The 4-p model on creativity, including person, process, press and product underlines that creativity is strongly connected with the materials employed to conceive and realize the creative outcome. As a multiform construct, it leads to a wide variety of approaches to study it. One of the most promising way to address this issue is to connect it with the cognitive development and related educational pathways, as creativity can be enhanced and stimulated in every child, leading to an improvement both at personal and societal level. Even if creativity is recognized and highly valued, there is still a lack of methods to stimulate creativity in an effective way, but useful hints may come from the outstanding contributions of Piaget and Montessori who underlined that the interaction with the physical world is a fundamental building block for cognitive development. In this paper, starting from these fixed points, we describe some methods to enhance creativity in children that give importance to the edge between digital and physical materials. Digital materials allow to open new ways to use physical materials and to integrate them in hybrid platforms that can used in educational contexts. Together with this perspective we provide the description of the application of these methodologies to enhance creativity in children with Autistic Spectrum Disorder.